Nerve Growth Factor Pathobiology During the Progression of Alzheimer’s Disease - Mufson, Elliott J.; Counts, Scott E.; Ginsberg, Stephen D.; Mahady, Laura; Perez, Sylvia E.; Massa, Stephen M.; Longo, Frank M.; Ikonomovic, Milos D. (Frontiers in Neuroscience, 2019)
The current review summarizes the pathobiology of nerve growth factor (NGF) and its cognate receptors during the progression of Alzheimer’s disease (AD). Both transcript and protein data indicate that cholinotrophic neuronal dysfunction is related to an imbalance between TrkA-mediated survival signaling and the NGF precursor (proNGF)/p75NTR-mediated pro-apoptotic signaling, which may be related to alteration in the metabolism of NGF. Data indicate a spatiotemporal pattern of degeneration related to the evolution of tau pathology within cholinotrophic neuronal subgroups located within the nucleus basalis of Meynert (nbM). Despite these degenerative events the cholinotrophic system is capable of cellular resilience and/or plasticity during the prodromal and later stages of the disease. In addition to neurotrophin dysfunction, studies indicate alterations in epigenetically regulated proteins occur within cholinotrophic nbM neurons during the progression of AD, suggesting a mechanism that may underlie changes in transcript expression. Findings that increased cerebrospinal fluid levels of proNGF mark the onset of MCI and the transition to AD suggests that this proneurotrophin is a potential disease biomarker. Novel therapeutics to treat NGF dysfunction include NGF gene therapy and the development of small molecule agonists for the cognate prosurvival NGF receptor TrkA and antagonists against the pan-neurotrophin p75NTR death receptor for the treatment of AD.